Pengembangan E-Modul Bahasa Indonesia Kelas Xii Dengan Flip Pdf Profesional Sebagai Alternatif Pembelajaraan Di Tengah Pandemi Covid 19 - Trisya Widiastutik (Balai Diklat Keagamaan Surabaya, 2021)
This study aims to develop an Indonesian Language E-Module XII grade of SMA / MA based on Flip PDF Professional. The research method used was R & D using the Borg & Gall model with the subjects of class XII students of MAN 2 Mojokerto. This model includes 10 steps, namely (1) researching and information collecting, (2) planning (3) develop preliminary form of product, (4) preliminary field testing, (5) operational field testing, (6) operational product revision (7) main field testing, 8) main product revision, (9) final product revision, and 10) dissemination and implementation. Due to limited time, the research was only carried out until the 7th step, namely main field testing. Based on the findings of this study, it is recommended that teachers use this E-Module as an alternative material for teaching learning process in the pandemic of Covid 19.